Physical and mechanical study of Palm Oil Fuel Ash (POFA) based geopolymer as a stabilizer for soft soil - Khasib, Isam Adnan; Nik Daud, Nik Norsyahariati (Universiti Putra Malaysia Press, 2020)
Construction of structures on soft soil is a challenging task and considered as one of the biggest concerns in geotechnical engineering. Binders that are environmentally friendly such as fly ash based geopolymer have been explored widely. In this study, the agro-waste material, Palm Oil Fuel Ash (POFA) was used to produce an environmentally friendly geopolymer binder to be used in soft soil stabilization. POFA was used in three ratios; 10%, 20% and 30% of dry weight of soil to produce geopolymer. Sodium hydroxide (NaOH) was used as an alkali activator at 12 molarity along with sodium silicate (Na2SiO3). Physical properties of soil (Atterberg Limits, Plasticity Index, and Linear Shrinkage Limit) and compaction assessment; before and after mixing with the geopolymer binder were investigated. The studied soil was classified as an inorganic high plasticity silt (MH), according to the Unified Soil Classification System (USCS). From compaction results; optimum moisture content (OMC) values showed a decreased pattern from 24.7% to 17.5%; and maximum dry density (MDD) increased from 1.37 Mg/m3 to 1.73 Mg/m3 for geopolymer with POFA ranging from 0% to 30% of the dry weight of soil, respectively. The optimum dosage of POFA based geopolymer was found to be 30% according to all tests mentioned. These properties suggest the potential use of the agro-waste based geopolymer binder to stabilize the soft soil.